Bridging the Gaps: A Bibliometric Key Theme Analysis in Multicultural Education Research (2019-2024) - Jobeda khanom; Tarequl Islam; Mahmudulhassan Mahmudulhassan (Bulletin of Islamic Research, 2025)
The goal of this study is to perform a thorough bibliometric analysis of multicultural education research. This study examines the field's publication trends, important themes, influential authors, and intellectual structure using a quantitative methodology. The Scopus database was used to gather a dataset of 744 papers published between 2019 and 2024.  Throughout the study period, the number of publications about multicultural education steadily increased, according to the analysis. Diversity, cultural competency, teacher preparation, and curriculum creation are among the major topics that have been recognized. In terms of research production, the United States surpassed the Netherlands and the United Kingdom as the top three nations. "Multicultural education," "diversity," and "cultural competence" were found to be key concepts in the area using network analysis using VOSviewer. The analysis also emphasized how multicultural education research is collaborative, with many studies including multinational collaborations.    The study's conclusions offer insightful information on the state of multicultural education research today. To support inclusive and equitable education for all students, researchers, educators, and policymakers can make well-informed judgments by being aware of the major trends, significant academics, and developing themes.